2022
DOI: 10.3390/su14095117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Economic Analysis of Heating Solutions for Rural Residences in China

Abstract: A spatial assessment is important to explore appropriate heating schemes for rural residences in China. Taking rural residences in six typical cities of China as the focus, four heating solutions, namely, coal-fired boiler heating systems (CBHS), wall-hung gas-fired boiler heating systems (GBHS), direct electric heating systems (DEHS), and air source heat pump systems (ASHPS), are compared and analyzed from the perspectives of primary energy consumption, environmental impact and heating costs. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Banks et al [28] reported the results of their research on heat-pump water-heating systems. Of interest is the research conducted by Zhang et al [29], which compares the primary energy consumption, environmental impact, and heating costs of coal-fired and wall-fired gas boiler heating systems, direct electric heating systems, and air-source heat pump systems using a life cycle analysis. The study by AlAli et al [30] exclusively focused on the United Arab Emirates and examined the energy efficiency of mosque buildings.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…Banks et al [28] reported the results of their research on heat-pump water-heating systems. Of interest is the research conducted by Zhang et al [29], which compares the primary energy consumption, environmental impact, and heating costs of coal-fired and wall-fired gas boiler heating systems, direct electric heating systems, and air-source heat pump systems using a life cycle analysis. The study by AlAli et al [30] exclusively focused on the United Arab Emirates and examined the energy efficiency of mosque buildings.…”
Section: The Literature Reviewmentioning
confidence: 99%